Can C-reactive protein levels increase the accuracy of the Ranson score in predicting the severity and prognosis of acute pancreatitis? A prospective cohort study - Başak, Fatih; Hasbahçeci, Mustafa; Şişik, Abdullah; Acar, Aylin; Tekesin, Kemal; Baş, Gürhan; Alimoğlu, Orhan (Turkish Journal of Gastroenterology, 2017)
Abstract Background/Aims: Acute pancreatitis (AP) is an acute inflammatory disorder of the pancreas, and its severe form affects nearly all systems of the body. The purpose of this study is to assess the Ranson score and the C-reactive-protein level as a novel model for prediction of the disease severity and mortality. Materials and Methods: A prospective cohort study was designed to evaluate the efficacy of the C-reactive-protein for the prediction of severe AP. We recorded the Ranson score and C-reactive-protein values in AP patients and determined the severity of the disease using the revised Atlanta classification. Four groups of criteria sets were created: Group 1: Ranson ≥3; Group 2: C-reactive-protein ≥150 mg/L; Group 3: Ranson ≥3 and C-reactive-protein ≥150 mg/L; Group 4: Ranson ≥3 or C-reactive-protein ≥150 mg/L. Identification of AP severity was accepted as the reference parameter for statistical analysis. Categorical variables were expressed as frequencies and percentages. The differences were considered as significant if the p value <0.05. Results: Six hundred and thirty-eight patients with AP were included in our study. We recovered a statistically significant difference in our assessment of the prediction of the severity of AP among the various groups (p=0.001). Our analysis revealed that group 4 had the highest sensitivity of 90.1% and 93.5% to differentiate moderately severe and severe AP from mild AP, respectively. Group 3 had the highest specificity of 97.1% for both moderately severe and severe AP. Conclusion: With the use of our new model, C-reactive-protein levels increase the efficacy of the Ranson score for predicting the severity of AP.